ANALISA DRUG RELATED PROBLEMS (DRPs) PADA PASIEN CHRONIC KIDNEY DISEASE (CKD) DI INSTALASI RAWAT INAP KLINIK SARI MEDIKA KABUPATEN SEMARANG: Analisa DRP pada pasien CKD - Poppy Diah Palupi; Veronika Jayaningsih (Jurnal Farmasi & Sains Indonesia, 2021)
Drug-Related Problems(DRPs) are unwanted events affecting patients related to treatment that can interfere with the success of therapy. This study aims to determine and analyze the DRPs that occur in Chronic Kidney Disease (CKD) patients in the Sari Medika Clinic, Semarang. This research is a descriptive study with retrospective design on CKD patients by taking samples using purposive sampling technique compared to the several Guidelines Pharmacotherapy Handbook 9th edition 2015, Kidney Disease Improving Global Outcomes (KDIGO), The Renal Drug Handbook Third Edition 2009, Clinical Practice Guide & Clinical Pathway for Heart Disease, Blood Vessels 2016, and Henry Ford Health System six edition 2011. The results of the study conducted on 84 CKD patients showed there were DRPs in 66 patients: Indication without therapy (30.86%), therapy without indication (6.17%), sub-therapeutic dose (1.23%), excessive drug doses (13.58%), improper drug selection (45.68%), and patients failing to receive drugs (2.47%).